Sistema acuapónico a escala piloto con chame (Dormitator Latifrons) y lechuga (Lactuca Sativa) para producción de alimentos, comunidad Casas Viejas, Cantón Bolívar. - Loor Morán, Gabriel Enrique (2018)
The objective of the research was to implement an aquaponic system on a pilot scale for the growth of the chame (Dormitator latifrons) and lettuce (Lactuca sativa) in the Casas Viejas, Calceta community. Non-experimental study, using bibliographic, descriptive and observational techniques, field visits, and surveys of 58 families. As a result, most are farmers; they grow corn; they consume drinking water from tankers, they have difficulty in their provision; they dedicate it to home consumption; they have minimum income and satisfaction for productive activity; they receive talks about food quality; they believe that production of organic avoids affectation to life, that the excessive use of chemicals generates future health problems; they produce healthy food; are aware of the environmental impact; they believe that water will one day be scarce and the use of monoculture affects soil fertility; they avoid burning pastures; they want to incorporate a food production system; they know about crops using aquaponic medium and that food production with this metod is good; the implementation of this will affect the production of sustainable food, as evidenced by the practical application of production and growth of chame (Dormitator latifrons) and lettuce (Lactuca sativa). Fish length and weight, and length of plants were analyzed, and a mass increase of 15% in grams was obtained with an average of 17cm. Regarding the plants, their cycle was completed in more than 75%. For the characterization of water quality, oxygen, Ph, nitrates, phosphate and others were taken into account. It is concluded that the aquaponic system studied is viable.